The neural basis of neuropsychiatric symptoms in Alzheimer’s disease - Zhang, Nicole K.; Zhang, Selena K.; Zhang, Li I.; Tao, Huizhong W.; Zhang, Guang-Wei (Frontiers in Aging Neuroscience, 2024)
Neuropsychiatric symptoms (NPS) such as depression, anxiety, apathy and aggression affect up to 90% of Alzheimer’s disease (AD) patients. These symptoms significantly increase caregiver stress and institutionalization rates, and more importantly they are correlated with faster cognitive decline. However, the neuronal basis of NPS in AD remains largely unknown. Here, we review current understanding of NPS and related pathology in studies of AD patients and AD mouse models. Clinical studies indicate that NPS prevalence and severity vary across different AD stages and types. Neuroimaging and postmortem studies have suggested that pathological changes in the anterior cingulate cortex, hippocampus, prefrontal cortex, and amygdala are linked to NPS, although the precise mechanisms remain unclear. Studies of AD mouse models have indicated that amyloid-beta and tau-related neurodegeneration in the hippocampus, prefrontal cortex, and anterior cingulate cortex are correlated with NPS-like behavioral deficits. A better understanding of the NPS phenotypes and related pathological changes will pave the way for developing a better management strategy for NPS in AD patients.